International accounting standardization practice in Hungary - Beke, Jenő (REGIONAL AND BUSINESS STUDIES, 2011)
The goal of this study is to describe and summarize the differences between national accounting rules and international standards and to evaluate and analyze their effects on business decisions, management performance, and the economic environment in Hungary. The unified, standardized accounting information system will lead to new types of analysis and data and the possible integration of new indicators from the business management of certain countries. It is very important for managers and researchers to evaluate and analyze the effects of international accounting standards on the business environment, especially on their contribution to harmonization and globalization. Financial data is from published financial statements and the Hungarian Business Information database. My sample comprises 65 international standards and 260 local accounting rules. This paper shows that both businesses earnings and stock returns affect management turnover. Businesses with lower labour productivity compared to their industry peers have greater incentives to adopt international accounting standards. National accounting rules are followed by firms with higher leverage and lagging sales growth and with more frequent employee layoffs. Standards user enterprises’ employee layoffs are more a response to accounting performance in the post-adoption period. However, the results on turnover are sensitive to this change in variable specification. So the increase in the sensitivity of turnover to accounting performance post-adoption is primarily driven by heightened turnover sensitivity to accounting losses. The results of applied regression model support the notion that a business structure wherein accounting earnings are linked to performance evaluations is more frequent in businesses working to adopt international accounting standards. Keywords: economics of accounting standards, business effects, standardization, harmonization, value based management